Kearifan Lokal Masyarakat Cangkringan dalam Melestarikan Agrowisata Jambu Madu Hijau sebagai Penunjang Ekonomi Lokal - Dewi Arsita (LP2M IAIN Sultan Amai Gorontalo, 2023)
Abstract: This study aimed to assess the pre-Covid-19 management of green guava agro-tourism and its post-Covid-19 resilience in Cangkringan Village, Banyundono District, Boyolali Regency. The study utilized a descriptive analysis approach to evaluate the revenue of Cangkringan Jambu Madu Hijau and employed SWOT analysis to examine both the internal factors, i.e., strengths and weaknesses, and the external factors, namely opportunities and threats of Cangkringan Agrotourism. The findings revealed that Cangkringan Jambu Agrotourism earned approximately Rp. 25,000,000 in 2020, while it generated approximately Rp. 100,000,000 in revenue after the COVID-19 pandemic (from April 2021 to June 2022). A viable strategy for Green Guava Agrotourism is the S-O approach, involving the expansion of agro-tourism offerings, including diverse photo opportunities and tourist attractions, alongside continuous promotional efforts. The S-T strategy entails showcasing the distinct features of Cangkringan Jambu Agrotourism and further enhancing product quality and marketing systems. W-O strategies emphasize the optimization and growth of agro-tourism, while W-T strategies revolve around offering discounts on products and agro-tourism entrance fees, along with enhancing the overall visitor experience. Keywords: Agrotourism; Income; Development; Strategy.